Charge Transport Mechanism in Thin Cuticles Holding Nandi Flame Seeds - Wycliffe K. Kipnusu; Gabriel Katana; Charles M. Migwi; I. V. S. Rathore; Joshua R. Sangoro (International Journal of Biomaterials)
Metal-sample-metal sandwich configuration has been used to investigate DC conductivity in 4 𝜇m thick Nandi flame [Spathodea campanulata P. Beauv.] seed cuticles. 𝐽-𝑉 characteristics showed ohmic conduction at low fields and space charge limited current at high fields. Charge mobility in ohmic region was 4.06×10−5(m2V−1s−1). Temperature-dependent conductivity measurements have been carried out in the temperature range 320 K <𝑇> 450 K. Activation energy within a temperature of 320 K–440 K was about 0.86 eV. Variable range hopping (VRH) is the main current transport mechanism at the range of 330–440 K. The VRH mechanism was analyzed based on Mott theory and the Mott parameters: density of localized states near the Fermi-level N(𝐸𝐹)≈9.04×1019(eV−1cm−3) and hopping distance 𝑅≈1.44×10−7 cm, while the hopping energy (𝑊) was in the range of 0.72 eV–0.98 eV.